Smart grid photovoltaic system pilot scale using sunlight intensity and state of charge (SoC) battery based on Mamdani fuzzy logic control - Kamil Faqih; Wahyu Primadi; Anik Nur Handayani; Ari Priharta; Kohei Arai (Journal of Mechatronics, Electrical Power, and Vehicular Technology, 2019)
The Utilization of renewable energy such as a photovoltaic system is the foremost alternative in transfers generated by conventional power plants, but the lack of photovoltaics is support for light intensity. The purpose of this research is to develop a pilot-scale smart grid photovoltaic system that can regulate the supply of electrical energy from either the battery or the power supply. The control system in this study uses the Mamdani fuzzy logic method in determining automatic system performance. This system monitors the intensity of light and battery which are then used as automatic safety parameters on the power supply, battery, and photovoltaic. The results of this study display the indicator results from the microcontroller in supplying electrical energy for the use of electrical loads, Power Supply has been served the load when the battery is in a low state which have a voltage 11 Volts, the battery has been served the load when the condition of the battery is in a medium and high condition which has a voltage of 11.5 ; ....; 13 Volts. PV has been served batteries or loads when the light intensity is cloudy and bright which have a light intensity of 3585 ; ...; 10752 Lux. This system can reduce dependence on conventional energy without reducing the quality of the energy supply at load and Photovoltaic system dependence on light intensity does not affect the supply of energy consumption to electrical loads.